DETERMINANTS OF PEPTIC ULCER DISEASE INCIDENCE IN PANGA SUB-DISTRICT, ACEH JAYA DISTRICT - Wahyuni, Srie; Khatimah, Husnul (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2024)
Peptic ulcer is one of the health problems in the community with a high prevalence. According to WHO in 2019 the incidence of gastric ulcers in the world reached 1.8 million to 2.1 million people each year. From the results of an initial survey conducted in the community of Panga sub-district, Aceh Jaya district. out of 10 people who had been interviewed, 8 people stated that they experienced gastric ulcers such as pain in the stomach. Research was conducted to determine the determinants of the incidence of gastric ulcers. This type of research is descriptive analytic with a cross sectional study approach. The independent variables are diet, coffee consumption, sleep patterns, stress levels, while the dependent variable is the incidence of gastric ulcers. The research was conducted in 2023. The population in the study was the community of panga sub-district, aceh jaya district as many as 156 people, while the sample was 112 students. The sampling technique used in the study was random sampling. The results of this study showed that diet and coffee consumption had a significant relationship with the incidence of peptic ulcers, while sleep patterns and stress levels had no significant effect. Regular coffee consumption can reduce the risk of peptic ulcer in the community of Panga District, Aceh Jaya Regency.